Inertial Force Sensing System for Partner Robots - Nonomura, Y.; Fujiyoshi, M.; Sugihara, H. (2006 5th IEEE Conference on Sensors, 2006)
An inertial force sensing system for partner robot control has been developed. We named this system MOST (MOtion Sensing Technology). The MOST consists of 3 angular rate sensors, 3 acceleration sensors, and a DSP (digital signal processor). The acceleration sensor is a semiconductor type and the angular rate sensor is a quartz type. The sensors have been made by MEMS (micro electro mechanical systems) technology for mass-produced cars. They are good for miniaturization of the sensing unit. Posture angle is generally obtained by integrating the angular rate over time. However, there was the divergence of the posture angle due to the offset output integration. New algorithm was proposed to suppress the divergence of the posture angle with the DSP in real-time. The performance of the sensing system, MOST, was demonstrated on the TOYOTA partner robots in the EXPO 2005 Aichi, Japan.